Implementation of the Translation Grammatical Method in Arabic Learning - Agus Salim; Aridlah Sendy Robikhah; Evi Zulianah; Fattahur Rokhimul Barik (Al-Mada: Jurnal Agama, Sosial, dan Budaya, 2022)
The learning method is one of the elements that must be met in the process of delivering material. The technique serves as a bridge between teachers and students and a lubricant to maximize learning. When teaching Arabic subjects, a teacher must master the material and have a high ability to convey material to students. For the learning process to take place effectively, the teacher learns to be observant in choosing the appropriate method to be applied so that the material can be appropriately conveyed and easily understood by students. The technique used in this research is Qualitative Field Research conducted at MTs Bahrul Ulum Blawi. As for the results of this study, the implementation of the Grammatical Tarjamah method at MTs Bahrul Ulum Blwi Class 7 has been going well. The learning process takes place in 3 stages: introduction, core activities, and closing. From the third stage, educators have adapted and carried out following the prepared RPP.